Determinant Factors Of Electric Bicycle Purchase Decisions: Evidence From Indonesia - Sulismawati, Sulismawati; Nuryana, Ida (LPPM ISNJ Bengkalis, 2024)
Changes in consumer behavior in electric bicycle purchases challenge sellers' ineffective marketing. This study aims to analyze the effect of price, promotion, and product quality on purchasing decisions for electric bicycles. This study uses a quantitative method with a survey approach as a research design. The population of this study was all buyers of electric bicycles at the Bismar Pasuruan Store, East Java, Indonesia, totaling 90 people. The sampling technique used purposive sampling so that the number of research samples was 40 people. The research sources were primary data from questionnaires via Google Forms and secondary data from literature studies. The data analysis technique used multiple linear regression with the help of the SPSS version 26 application. The study's results showed that price, promotion, and product quality positively affected purchasing decisions for electric bicycles. This study can complement existing theories and be a reference for further research. Practically, this study can be a reference for the industry in terms of pricing strategies, compelling promotions, and improving the quality of electric bicycles as product marketing.